Crohn’s disease: etiopathogenic and surgical considerations on the subject of a personal series - Piñeyro, Alberto; Carriquiry, Luis (Cirugía del Uruguay, 2002)
The paper contains a retrospective analysis of a series of 20 surgical acts in patients suffering from Crohn's disease, performed by the authors over a 13-year period. Cronh' disease is an inflamatory, granulomatose, transmural and pan digestive. The paper discusses the result of complex interaction of genetic susceptibility, enviroment and immunitary system. In this XXI Century it still remains as a disease that may be treated, but is incurable. Even though at the onset treatment is medical, 80% of patients shall require at least one operation during its evolution. Resection is the elective surgery vis-á-vis a primary or recurrent disease.